Indiana Jones and the kingdom of the crystal skull - Marshall, Frank; Lucas, George, 1944-; Nathanson, Jeff.; Koepp, David; Spielberg, Steven, 1946-; Ford, Harrison, 1942-; Blanchett, Cate, 1969-; Allen, Karen, 1951-; LaBeouf, Shia, 1986-; Winstone, Ray, 1957-; Hurt, John, 1940-; Broadbent, Jim.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Teaming up with a rebellious young biker and his spirited love Marion, Indy tries to outrace a brilliant and beautiful agent for the mystical, all-powerful Crystal Skull of Akator.
Widescreen.
Based on the characters created by George Lucas and Philip Kaufman.
Special features: "The return of a legend" featurette; pre -production featurette.
For private home use only.
Director of photography, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams ; costume designers, Bernie Pollack, Mary Zophres ; production designer, Guy Hendrix Dyas.
Harrison Ford, Cate Blanchett, Karen Allen, Shia LaBeouf, Ray Winstone, John Hurt, Jim Broadbent.
Keywords: Jones, Indiana (Fictitious character) -- Drama; Adventure and adventurers -- Drama; Crystals -- Drama; Indiana Jones films; Films for the hearing impaired; Feature films; Action and adventure films